Problems and perspectives of Russian financial control development in a globalization condition - T. P. Voronchenko (Путеводитель предпринимателя, 2020)
In the article the peculiarities of the modern Russian system of financial control, the characteristics and the evaluation of its status, systematic problems and outlined the prospects of its development in conditions of globalization.